2019
DOI: 10.3390/ma12030380
|View full text |Cite
|
Sign up to set email alerts
|

Particulated, Extracted Human Teeth Characterization by SEM–EDX Evaluation as a Biomaterial for Socket Preservation: An In Vitro Study

Abstract: The aim of the study was to evaluate the chemical composition of crushed, extracted human teeth and the quantity of biomaterial that can be obtained from this process. A total of 100 human teeth, extracted due to trauma, decay, or periodontal disease, were analyzed. After extraction, all the teeth were classified, measured, and weighed on a microscale. The human teeth were crushed immediately using the Smart Dentin Grinder machine (KometaBio Inc., Cresskill, NJ, USA), a device specially designed for this proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…In an animal experiment, it was shown that mineralized dentin particles present intra and extra pores up to 44.48%. This porosity increases the blood supply and supports slow resorption of the grafted material, thereby supporting healing and replacement resorption to achieve lamellar bone [27]. Interestingly, in the present study, socket grafting with MPDA/PRF resulted in a slight increase in both the buccal and lingual bone heights.…”
Section: Discussionsupporting
confidence: 59%
“…In an animal experiment, it was shown that mineralized dentin particles present intra and extra pores up to 44.48%. This porosity increases the blood supply and supports slow resorption of the grafted material, thereby supporting healing and replacement resorption to achieve lamellar bone [27]. Interestingly, in the present study, socket grafting with MPDA/PRF resulted in a slight increase in both the buccal and lingual bone heights.…”
Section: Discussionsupporting
confidence: 59%
“…Demineralized dentin (4) and Freeze Dried Dentin (5) have been more extensively researched and certainly they have a secure place as graft materials. But the processing of these materials takes place in a laboratory and the extracted teeth are cannot be immediately used.…”
Section: Discussionmentioning
confidence: 99%
“…With this process the particles need to be additionally conditioned/disinfected with chemicals following special protocol, so the new dentin particles could be inserted in the extraction socket. Calvo-Guirado et al (5) concluded that in this way bone grafts could be considered to be an attractive option due to their autogenous origin and favorable clinical results, which have shown that these materials offered good osteoinductive capacities. The particulate tooth material provides excellent biocompatibility without eliciting an immune response or a foreign material reaction, or infection after it is used.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen New Zealand white rabbits were included in this study. Inclusion criteria were: pathogen-free male, with an initial weight of 3.500-4.000 g and aged 26-28 weeks to ensure skeletal maturity and physical closure [23,24]. Ethical approval for the experiment was obtained from the Ethics Committee in Animal Research of the University of Murcia (A13150102).…”
Section: Animal Selection and Conditioningmentioning
confidence: 99%